Penerapan Case Tracking System dalam Pengelolaan Arsip di Pengadilan Negeri 1A Padang - Nugraha, Anja; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
Writing this paper aims to describe: (1) the application of Case Tracking System in records management in the High Court of Class 1A Padang, (2) constraints application of Case Tracking System in records management in the High Court of Class 1A Padang, (3) measures to be done so that the application of Case Tracking System in records management in Class 1A High Court of Padang goes well. Based on the results of wording can be concluded as follows. First, the activities in the application of Case Tracking System in records management in the High Court of Padang as Class 1A, archive storage systems, fixtures in records management, the system used in records management and retrieval. Secondly, there are still obstacles encountered in the implementation of Case Tracking System in records management in Class 1A High Court of Padang like, human resources, equipment, upgrade applications and Internet network access. Third, efforts were made in implementation Case Tracking System in records management in Class 1A High Court of Padang like, improve human resources, improving infrastructure, training to upgrade applications and improve network.Â Keywords:Case Tracking System, records,managementÂ